The Influencing Factors on Teacher’s Turnover Intention of Higher Vocational Education in Xiamen, China - Lin Weiyi; Khunanan Sukpasjaroen (Migration Letters, 2023)
This study conducted an in-depth analysis of the factors influencing emotional exhaustion and turnover intention among teachers in vocational colleges in Xiamen, China. The researcher formulated six research objectives as follows: To assess the prevalence of turnover intention among teachers in higher vocational education institutions in Xiamen, China. To explore the relationship of Surface Acting, Deep Acting, Automatic Emotional Regulation, Coworker Incivility, and Caring Climate on Emotional Exhaustion, and its subsequent impact on Turnover Intention. To examine the relationship between Emotional Exhaustion and Turnover Intention. To investigate the mediating effect of Emotional Exhaustion between Surface Acting, Deep Acting, Automatic Emotional Regulation, Coworker Incivility, Caring Climate, and Turnover Intention. To explore potential gender, educational background, or professional title differences in the experience of turnover intention. To develop a causal model of influential factors influencing teachers’ turnover intention in higher vocational education in Xiamen, China. In this study, the researcher employed a quantitative research approach and conducted a questionnaire survey among nine vocational colleges in Xiamen, China, involving a target population of 3145 individuals. Following the sampling method proposed by Yamane (1967), a minimum of 355 questionnaires needed to be distributed. Therefore, to ensure the authenticity and effectiveness of the research, the researcher utilized a stratified random sampling method, resulting in a total of 710 questionnaires being distributed. In the data analysis process, the researcher employed methods including reliability analysis, validity analysis, correlation analysis, difference analysis, common method bias, and structural equation modeling (path analysis and mediation analysis). Finally, the researcher obtained the following results: This research found the current situation of turnover intention among teachers at higher vocational colleges in Xiamen; Surface acting, deep acting, automatic emotional exhaustion, and coworker incivility have significant positive influences on emotional exhaustion. Caring climate has a significant negative influence on emotional exhaustion. Similarly, surface acting, deep acting, automatic emotional exhaustion, and coworker incivility have significant positive influences on turnover intention. Caring climate has a significant negative influence on turnover intention; Emotional exhaustion has a significant positive influence on turnover intention; There is a mediating effect of emotional exhaustion between surface acting, deep acting, automatic emotional regulation, coworker incivility, caring climate, and turnover intention; There is the potential influence of gender, educational background, and job title differences on turnover intention; This study constructed a causal model of the factors influencing turnover intention among teachers at higher vocational colleges in Xiamen.